(untitled) (Research, Society and Development, 2021)
Objective: Systematize the experience experienced by nursing students in the telemonitoring of patients suspected and/or confirmed of COVID-19, through the strategic action "Brazil Counts With Me" in primary care in Manaus. Methods: This is a qualitative, descriptive study based on the methodology of systematization of the experience proposed by Holliday, using, for this, observation records and notes, contacts with other health professionals, health education strategy with SUS users, collective learning of new knowledge and practices in coping with COVID –19, held from May to December/2020 in the telesaude sector of the Manaus Municipal Health Department, opportunistic by a strategic action, known as "Brazil Counts With Me" of the Ministry of Health. Results: The experience showed that telemonitoring, in the pandemic scenario, helped in the dissemination of information and problem solutions without the need to travel to hospital services. It instigated the search for new knowledge about technological tools of teaching and learning, as well as the use of technical health, as an effective alternative that facilitates communication with the patient without physical contact and provides a comfortable and safe environment for dignified health care, thus fulfilling the principles of the SUS. Conclusion: The telemonitoring service worked effectively during social isolation, serving as an academic training strategy, besides serving as an alternative to the population that faces weaknesses related to socio-economic aspects and access to health services.